2008
DOI: 10.1212/01.wnl.0000317094.86209.cb
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and brain atrophy in early Alzheimer disease

Abstract: Objective-Examine the correlation of cardiorespiratory fitness with brain atrophy and cognition in early-stage Alzheimer's disease (AD).Background-In normal aging physical fitness appears to mitigate functional and structural agerelated brain changes. Whether this is observed in AD is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
307
4
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(342 citation statements)
references
References 45 publications
23
307
4
8
Order By: Relevance
“…Finally, (Dutsman et al, 1990;Hilman et al, 2003) an increased cerebral blood flow was observed in zones related directly to verbal learning and memory. These benefits extended to Alzheimer´s patients to a to a greater aerobic capacity in those that have less brain atrophy than subjects who are not in shape (Burns et al, 2008;Heyn et al, 2004). Additionally, postmenopausal women in good physical shape, independent from HRT (hormone replacement), show an increase in cognition and brain volume than women that are less physically fit (Ericson et al, 2007).…”
Section: Effects Of Physical Exercise On the Cognitive Abilitymentioning
confidence: 99%
“…Finally, (Dutsman et al, 1990;Hilman et al, 2003) an increased cerebral blood flow was observed in zones related directly to verbal learning and memory. These benefits extended to Alzheimer´s patients to a to a greater aerobic capacity in those that have less brain atrophy than subjects who are not in shape (Burns et al, 2008;Heyn et al, 2004). Additionally, postmenopausal women in good physical shape, independent from HRT (hormone replacement), show an increase in cognition and brain volume than women that are less physically fit (Ericson et al, 2007).…”
Section: Effects Of Physical Exercise On the Cognitive Abilitymentioning
confidence: 99%
“…Moreover, there is increasing evidence to support an inverse relationship between cardiorespiratory fitness and brain atrophy in the earliest clinical stages of AD. Higher fitness levels in early AD patients were associated with preserved brain volume (less brain atrophy) independent of age 5 . Several studies have shown that physical training programs may have a role in the improvement of ADL, quality of life, depressive symptoms, and motor and cognitive function in patients with AD 3,4,[6][7][8][9][10][11] .…”
mentioning
confidence: 91%
“…Memory is the cognitive domain most significantly impaired in MCI and in early stages of dementia, whereas executive functions tend to falter in the later stages of AD [6,64]. Recent MRI studies have reported an association between medial temporal deterioration and cardiovascular fitness [17] and an association between increased cardiovascular fitness and reduced brain atrophy in AD [16]. The spectrum of physical training interventions adopted in these trials included Tai Chi, flexibility, relaxation, balancing techniques, and varying intensities of aerobic exercise and strength training.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity that targets cardiovascular fitness (peak VO 2 ) may offer neuroprotective benefits and attenuate the neuronal structural and functional changes that are associated with MCI and dementia [15][16][17]. Evidence from animal models has demonstrated that aerobic exercise can increase neurogenesis, angiogenesis, learning, and memory in rats [18,19] and inhibit the progression of Alzheimer's-related neuropathology in mice [20].…”
Section: Introductionmentioning
confidence: 99%